Spatial and Temporal Analysis of Corrosion and Scaling Trends in Zanjan Water Distribution Network Using GIS, Iran - Farhad Ghayurdoost; Javad Mohammadi; Ali Assadi (Iranian Journal of Health, Safety and Environment, 2019)
Corrosion and scaling of piping are a main issue in the operation of the drinking water network. Corrosive water can cause the intrusion of heavy metals into water and can lead to affect public health. This study aims to present the corrosion and scaling potential of Zanjan drinking water network that is located in north west of Iran. This descriptive cross-sectional study was carried out using calculation of Langlier Saturation Index (LSI), Ryznar Stability Index (RSI), Puckorius Scaling Index (PSI), and Aggressiveness index (AI). Thirty six samples were taken from all over the city within two seasons, summer and autumn in 2016. To reach this goal following parameters such as pH, total dissolved solids (TDS), alkalinity, calcium hardness, magnesium, total hardness, temperature and electrical conductivity (EC) in all samples were measured in the laboratory. The mean and standard deviation values of LSI, RSI, PSI and AI indices were equal to -0.62±0.18, 8.26±0.29, 8.04±0.51 and 11.5±0.24, respectively in summer and -0.83±0.12, 8.70±0.33, 8.00±0.29 and 11.15±0.25, respectively in autumn. According to all indices the results have shown that Zanjan drinking water is a mild corrosive. Finally, it is recommended that water authorities must be adjusted effective parameters such as pH of treated water at the beginning of the network in order to corrosion control.